Preparation of Different Carbon Materials by Thermochemical Conversion of Lignin - Rosas, Juana M.; Berenguer, Raúl; Valero-Romero, María José; Rodríguez-Mirasol, José; Cordero, Tomás (Frontiers in Materials, 2014)
Lignin valorization plays a crucial role within the modern biorefinery scheme from both the economic and environmental points of view; and the structure and composition of lignin becomes it an ideal precursor for the preparation of advanced carbon materials with high added-value. This review provides an overview of the different carbonaceous materials obtained by thermochemical conversion of lignin, such as activated carbons, carbon fibers, template carbons; high ordered carbons; giving information about the new strategies in terms of the preparation method and their possible applications.